OʻZBEKISTONDA SAKRAL GEOGRAFIYANI RIVOJLANTIRISh ISTIQBOLLARI - Safarov, I.B. (SCIENCE and SOCIETY, 2025)
This article analyses the prospects for the development of sacred geography in Uzbekistan. The article also covers the issues of preserving and developing sacred monuments, expanding tourism, and developing international cooperation.
Keywords: sacred geography; culture; tourism; religious monuments; historical monuments; tourism potential; international cooperation